Ultra-sensitive molecular detection of gene fusions from RNA using ASPYRE - Eleanor R Gray; Justyna M Mordaka; Efthimia R Christoforou; Kristine von Bargen; Nicola D Potts; Christina Xyrafaki; Ana-Luisa Silva; Magdalena Stolarek-Januszkiewicz; Katarzyna Anton; Paulina K Powalowska; Simonetta Andreazza; Alessandro Tomassini; et al. (BMC, 2022)
Abstract Background RNA is a critical analyte for unambiguous detection of actionable mutations used to guide treatment decisions in oncology. Currently available methods for gene fusion detection include molecular or antibody-based assays, which suffer from either being limited to single-gene targeting, lack of sensitivity, or long turnaround time. The sensitivity and predictive value of next generation sequencing DNA-based assays to detect fusions by sequencing intronic regions is variable, due to the extensive size of introns. The required depth of sequencing and input nucleic acid required can be prohibitive; in addition it is not certain that predicted gene fusions are actually expressed. Results Herein we describe a method based on pyrophosphorolysis to include detection of gene fusions from RNA, with identical assay steps and conditions to detect somatic mutations in DNA [1], permitting concurrent assessment of DNA and RNA in a single instrument run. Conclusion The limit of detection was under 6 molecules/ 6 µL target volume. The workflow and instrumentation required are akin to PCR assays, and the entire assay from extracted nucleic acid to sample analysis can be completed within a single day.